Application of swarm intelligence technique to learning scenario personalization - Žilinskienė, Inga; Kubilinskienė, Svetlana (Lietuvos matematikos rinkinys, 2012)
The paper is aimed to analyse learning scenario personalization according to learning styles. In order to do that swarm intelligence technique is discussed and modified ant colony optimization method is suggested. Computer simulation is carried out to verify its suitability to the problem of learning scenario personalization. The results of the computer simulation is presented and parameters custamization, long cold-start problems are discuseed.
Keywords: learning scenario; personalization; learning style; swarm intelligence; e-learning